Karakuri Kaizen Design to Reduce Work Time at the Packing Station - Mauluddin, Yusuf; Fardiansyah, Bagas (Spektrum Industri, 2025)
This study investigates production bottlenecks at the packing station of PT Anta Boga Pangan Nusantara, where manual operations resulted in prolonged cycle times and reduced efficiency. The research aims to design and implement a Karakuri Kaizen–based Lean Mover to minimize work time and enhance process performance. A quantitative approach was employed, involving direct observation, time measurement, and process analysis. The implementation of the Lean Mover successfully reduced the cycle time from 158.08 seconds to 24.74 seconds, outperforming the target takt time of 27 seconds. These findings demonstrate that low-cost, energy-efficient mechanical systems can effectively eliminate non-value-added activities, balance operator workloads, and improve productivity in food industry operations. The novelty of this study lies in the application of Karakuri Kaizen within the food manufacturing sector, a field rarely explored in previous research, thereby extending its applicability beyond conventional industrial settings. The study contributes theoretically by providing empirical evidence of Karakuri Kaizen’s effectiveness in optimizing manual operations in resource-constrained environments, and practically by offering an ergonomic, sustainable, and affordable alternative to high-cost automation systems.